The contribution of age and time-to-death on health care expenditure for out-of-hospital services - Moorin, Rachel; Gibson, D.; Holman, D'A.; Hendrie, Delia (The Royal Society Medicine Press Ltd, 2012)
Objectives: Controversy persists over the relationships between health care expenditure, time-to-death and age, undermining attempts to generate convincing predictions for policy. This paper explores the relationships between time-to-death (TTD), age and health care expenditure for Australian Medicare-funded, out-of-hospital services in the last five years of life, assessing if the relationship varies across different types of out-of-hospital services. Methods: Medicare Benefit Scheme claims for five years before death in Western Australia (1990 – 2004)pertaining to out-of-hospital primary care, specialist or diagnostic and therapeutic services were used to determine the total and mean per capita health care expenditure (HCE) according to age and TTD. Data were evaluated using univariate linear regression (age) and segmented time-trend regression analysis (time-to-death). Results: Changes to out-of-hospital HCE in the last five years of life did not consistently show a positive association with changes in the number of decedents. Only primary care services demonstrated a linear relationship for HCE and age. For TTD, a linear relationship was observed for all three service types within each retrospective period. Conclusions: This study has identified significant differences in the relationship between age, TTD and out-of- hospital HCE across service type, further highlighting potential shortcomings in methods that use single, all- service, all-cause models to predict future HCE. These results build on our previous study and suggest that such predictions should either use separate models, or models capable of accounting for the different relationships of HCE with TTD and age across types of services in order to predict future HCE more accurately.